Дистанционное образование в период пандемии: предваритель- ные итоги (электронное обучение русскому языку как иностранному в техни- ческом вузе) - Дикова, Татьяна (Acta Polono-Ruthenica, 2021)
The article discusses the capabilities of the electronic educational platform Microsoft Teams in the context of distance learning when teaching Russian as a foreign language. Among the positive aspects, there are opportunities for feedback from students. At the same time, a decrease in motivation for learning, the complexity of checking written assignments and control is shown. In general, the capability of this platform is characterized as supplementary in relation to traditional face-to-face training.